Improvement of Quality of Life after Surgical Treatment of Patients with MRONJ: A Prospective Analysis Using the SF-12 and OHIP-14 Questionnaires - Georg Hoene; Nikolaus von Hahn; Denise Sievers; Lukas Schuffelen; Susanne Wolfer; Kathi Goldstein; Boris Schminke; Phillipp Brockmeyer; Philipp Kauffmann (International Journal of Dentistry)
Background. Medication-related osteonecrosis of the jaw (MRONJ) is a rare, serious, and debilitating disease of unknown cause that can be associated with significant health-related quality of life (HRQOL) impairment. Hematological disease is characterized by a nonhealing exposed jawbone in patients with a history of antiresorptive or antiangiogenic agent use without radiation exposure to the head or neck. Patients and Materials and Methods. This prospective study over the period from May 2020 to December 2021 included a representative sample consisting of 27 patients with at least stage 2 MRONJ lesions who underwent surgical rehabilitation via oral and maxillofacial surgery at the University Medical Center Göttingen, Germany. Quality of life data were collected over a 6-month postoperative period using the Health-Related QOL (SF-12) and Oral Health-Related QOL (OHIP-14) questionnaires. Results. A total of 27 patients considered in the study had a total of 42 MRONJ lesions, corresponding to a mean of 1.56 necroses per patient. MRONJ lesions were downstaged in 85% of the patients. HRQOL was evaluated with the SF-12 questionnaire. Significant improvements were found in six of the eight categories (General Health (p <0.001), Bodily Pain (p<0.001), Mental Health (p<0.001), Vitality (p <0.001), Role-Emotional (p=0.028), and Social Functioning (p=0.031)). The OHRQOL score also improved significantly after surgical intervention (p<0.001). Conclusion. With completed surgical therapy, improvements in HRQOL and OHRQOL are measurable.